2015
DOI: 10.1063/1.4921649
|View full text |Cite
|
Sign up to set email alerts
|

Dye aggregation identified by vibrational coupling using 2D IR spectroscopy

Abstract: We report that a model dye, Re(CO)3(bypy)CO2H, aggregates into clusters on TiO2 nanoparticles regardless of our preparation conditions. Using two-dimensional infrared (2D IR) spectroscopy, we have identified characteristic frequencies of monomers, dimers, and trimers. A comparison of 2D IR spectra in solution versus those deposited on TiO2 shows that the propensity to dimerize in solution leads to higher dimer formation on TiO2, but that dimers are formed even if there are only monomers in solution. Aggregates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(102 citation statements)
references
References 49 publications
6
96
0
Order By: Relevance
“…Investigations concentrated on coupling between linear- and bridged-bound diatomic adsorbates 31 or different types of functional groups attached to self-assembled organic monolayers 14,25,26,29,30 . The only exception are closely packed metal-carbonyl molecules at semiconductor surfaces, for which band splitting and vibrational energy transfer has been observed that were related to aggregation of the sample at the interface 32,33 . The reason why interactions between adsorbates at interfaces are so hard to observe is largely unresolved to date.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations concentrated on coupling between linear- and bridged-bound diatomic adsorbates 31 or different types of functional groups attached to self-assembled organic monolayers 14,25,26,29,30 . The only exception are closely packed metal-carbonyl molecules at semiconductor surfaces, for which band splitting and vibrational energy transfer has been observed that were related to aggregation of the sample at the interface 32,33 . The reason why interactions between adsorbates at interfaces are so hard to observe is largely unresolved to date.…”
Section: Introductionmentioning
confidence: 99%
“…These observations indicate that first, the coupling between molecules is weak, and that second, each molecule exists as a single species on the surface, in contrast to previous related studies, which differ in the way how the samples have been prepared. [37][38][39] But even when coupling is too weak to result in direct cross-peaks at early population times, vibrational energy transfer may occur as a result of fluctuations in the coupling Hamiltonian (in analogy to NOESY in NMR), that reveals cross-peaks growing in as a function of population time. 20,[40][41][42] To explore that effect, Figure 4 shows a time-series of 2D ATR IR spectra, where indeed distinct cross-peaks show up above and below the diagonal after a few picoseconds ((b) -(d)).…”
mentioning
confidence: 99%
“…20 Since we however do not observe any direct cross peak, we assume that Eq. 3 overestimates the coupling, which is counter-balanced by the fact that cross-relaxation can proceed to more than one coupling partner on the surface (the model Despite significant efforts reported in literature 30,[47][48][49] , intermolecular couplings of surface-bound molecules have only rarely been observed 38 , and the estimates given above help to understand why that is so. In the present case, we can observe cross peaks with good signal-to-noise ratio, but this is since we have the very strong transition dipole of the symmetric stretch vibration of a metal-carbonyl together with (presumably) a close to optimal packing on the surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2D IR spectroscopy has successfully addressed a myriad of challenges in biophysics and materials sciences, from measuring the conformations and dynamics of proteins [16] and amyloid fibrils [7] to revealing excitonic structures of dye monolayers that have implications in solar cell design [8]. There are many optical designs of 2D IR spectrometers, but all require three interactions between the laser pulses and the molecules.…”
mentioning
confidence: 99%